RESPONSE OF ORGANIC FERTILIZER OF BAMBOO BAMBOO AND VEGETABLE COMPOST ON VEGETATIVE GROWTH OF ROBUSTA COFFEE (CoffeaCanephora) - Siregar, Elda Sari; Ritonga, Eka Nurwani; Mahmud, Amir; Harahap, Maya Desriyani (Talenta Publisher, 2022)
This research program aims to determine the responsegiving organic fertilizer to the vegetative growth of robusta coffee plants (CoffeaCanephora). Using a 2 factorial Group Design (RAK), each treatment was given 3 replications. Factor 1 was liquid organic fertilizer for bamboo shoots (P0: control, P1: 200 ml + 1000 ml water, P2: 500 ml + 1000 ml water, and P3: 800 ml + 1000 ml water). Factor 2 is using vegetable compost (K0: control, K1: 10 grams/polybag, K2: 20 grams/polybag), K3: 30 grams/polybag). Parameters observed were plant height, number of leaves, stem diameter, and leaf width. Based on the data on the response variance of the application of liquid organic fertilizer (POC) for bamboo shoots, it was shown that there was no significant effect on the parameters of plant height, number of leaves, stem diameter, and leaf width at the ages of 2, 4, 6, 8, 10, 12 mst. The results of the response variance data for the application of vegetable compost showed no significant effect on the parameters of plant height, number of leaves, stem diameter, and leaf width at the ages of 2, 4, 6, 8, 10, 12 mst. And the results of the interaction of the two treatments showed no significant effect on the parameters of plant height, number of leaves, stem diameter, leaf width.